Eugenia veadeirensis, a new species of Myrtaceae from the highlands of Goiás (Central Brazil) and new miscellaneous records for the Brazilian flora - Villarroel, Daniel; Faria, Jair E. Q.; Quevedo, Ana W.; Lopez, Mercy; Miranda, Vanessa; Klitgaard, Bente B.; Proença, Carolyn E. B. (Phytotaxa, 2018)
We describe Eugenia veadeirensis, a new species endemic to the Chapada dos Veadeiros from Brazil. The species most similar to E. veadeirensis is E. michaelneei. However, there are 14 morphological characteristics which differentiate them. In addition, we report Aspilia cardenasii, Bougainvillea praecox, Calea rhombifolia, Cleistocactus samaipatanus, Dimerostemma asperatum and Varronia multicapitata as new records for the Brazilian flora.